1998
DOI: 10.1590/s1020-49891998000500001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de anemia en gestantes, Hospital Regional de Pucallpa, Perú

Abstract: Las encuestas demográficas de salud y población del Perú indican que las tasas globales de fecundidad, la proporción de adolescentes embarazadas y la mortalidad maternoinfantil son más altas en la selva que en otras zonas del país. Las parasitosis intestinales endémicas agra nacidos. Ni esta tasa ni el peso de los recién nacidos resultaron asociados con el grado de anemia de la madre. El análisis de regresión multivariado muestra que el peso de la madre al inicio de la gestación (P = 0,0001), el peso ganado du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
4
1
12
Order By: Relevance
“…The prevalence is considerably lower than that previously reported from India (84.9%),6 Nigeria (40.4%),11 Jimma town, southwest Ethiopia (41.9%),12 Peru (70.1%),17 and China (58.6%) 19. The present study findings of anemia were also lower than that stated in Ethiopian demographic and health survey reports of 2005, namely, 30.6% 8.…”
Section: Discussioncontrasting
confidence: 77%
“…The prevalence is considerably lower than that previously reported from India (84.9%),6 Nigeria (40.4%),11 Jimma town, southwest Ethiopia (41.9%),12 Peru (70.1%),17 and China (58.6%) 19. The present study findings of anemia were also lower than that stated in Ethiopian demographic and health survey reports of 2005, namely, 30.6% 8.…”
Section: Discussioncontrasting
confidence: 77%
“…Prevalence of anemia in pregnancy varies from country to another and from region to another. Previous studies reported that the prevalence of anemia among pregnant women was 20.1% (hemoglobin < 11.0 g/dL in the first and third trimesters or < 10.5 g/dL in the second trimester of pregnancy) in Thailand [19], 13% (Anemia was defined using the 5th percentile cutoff for each week of gestational age as proposed by Yip from the Centers of Disease Control, 1989) in Puente Alto, Chile [20], 30.2% (hemoglobin < 10.5 g/dL) in Korea [21], 19.7% in South Africa [22], 34.4% (hemoglobin < 11 g/dL) in Venezuela [23], 35.3% (hemoglobin < 11 g/dL) in Lagos, Nigeria [24], 70.1% in Peru [25], 41.9% in Jima town Ethiopia [26], 55% (hemoglobin < 11 gm/dL) in Sharkia Governorate, Egypt [27], 25.8% in North of Iran [28], 31.9% (hemoglobin < 11 g/dL) in Asir region, Saudi Arabia [29], 16.7% (hemoglobin < 11 g/dL) in Southern Iran [30], and 42% in Northern Jordan [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of these factors are closely related to both poverty and anemia, as has been reported in other studies. 14,[31][32][33][34] The increased prevalence of anemia associated with parity could be due to a progressive depletion of nutritional stores during pregnancy, that has been documented in women of other developing countries. [34][35][36] Additional variables not evaluated in this analysis should be taken into account, such as dietary factors including intake of foods with lower iron biodisponibility and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%